IMPLEMENTASI KEBIJAKAN VAKSINASI DALAM TINJAUAN MSN APPROACH (Analisis System Approach Pada Pelaksanaan Vaksinasi Dalam Rangka Penanggulangan Covid-19 Di Kota Pekanbaru Pada Tahun 2021) - Melsy Oktary; Hasim As’ari (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
In 2020, the whole world is affected by the COVID-19 pandemic, including Indonesia. Covid-19 is very dangerous for the community due to the rapid increase in the number of people affected by Covid-19 in Indonesia, including in the city of Pekanbaru. Pekanbaru City is one of the most densely populated cities so it is easy for this virus to spread, Pekanbaru City has been included in the highest cases of Covid-19, many people have been exposed to Covid-19. The high spread of Covid-19 in the community has prompted the Indonesian government to issue Regulation of the Minister of Health Number 10 of 2020 concerning the Implementation of Vaccination in the Context of Combating the Corona Virus Diease (Covid-19) Pandemic. This vaccination policy aims to reduce transmission, reduce morbidity and mortality, achieve group immunity in the community, protect the community from Covid-19 so that they remain socially and economically productive. In this study using qualitative methods with data collection techniques by observation, interviews, and documentation. The data were analyzed qualitatively using the theory of Yulianto Kadji policy implementation model, namely MSN-Approach (Mentaliti, System, Networking) using the system-approach indicator. The results of this study based on system-approach indicate that the implementation of the vaccination policy has been going quite well but in its implementation there are still obstacles and rejections, namely there are still elderly people who have not been vaccinated, limited vaccine stock, long queues for vaccine implementation.